2015
DOI: 10.1080/15384047.2015.1017155
|View full text |Cite
|
Sign up to set email alerts
|

Activity of the novel dual phosphatidylinositol 3-kinase/mammalian target of rapamycin inhibitor NVP-BEZ235 against osteosarcoma

Abstract: Keywords: MEK/Erk and chemo-resistance, NVP-BEZ235, osteosarcoma, PI3K-Akt-mTOR signaling Abbreviations: mammalian target of rapamycin (mTOR); mTOR complex 1 (mTORC1); mTOR complex 2 (mTORC2); phosphoinositide-dependent protein kinase-1 (PDK1); phosphatidylinositol 3-kinase (PI3K); receptor tyrosine kinases (RTKs).Recent studies have identified that constitutively active phosphatidylinositol 3-kinase (PI3K)/Akt/mammalian target of rapamycin (mTOR) signaling is an important feature of osteosarcoma, where it pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
59
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(60 citation statements)
references
References 41 publications
1
59
0
Order By: Relevance
“…We studied the potential effect of XL388 on OS cell apoptosis. As described in our previous study [3], three independent apoptosis assays, including TUNEL staining assay, caspase-3 activity assay and histone DNA ELISA assay, were applied. Results from these assays demonstrated that XL388 induced significant apoptosis activation in MG-63 cells (Figure 2A–2C).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We studied the potential effect of XL388 on OS cell apoptosis. As described in our previous study [3], three independent apoptosis assays, including TUNEL staining assay, caspase-3 activity assay and histone DNA ELISA assay, were applied. Results from these assays demonstrated that XL388 induced significant apoptosis activation in MG-63 cells (Figure 2A–2C).…”
Section: Resultsmentioning
confidence: 99%
“…XL388 showed a dose-dependent effect in promoting MG-63 cell apoptosis (Figure 2A–2C). To study the effect of apoptosis in XL388-induced cytotoxicity, various caspase-dependent apoptosis inhibitors were utilized [3]. As demonstrated, the pan-caspase inhibitor (z-VAD-fmk, vad), the caspase-3 specific inhibitor (z-DVED-fmk, dved) and the caspase-8 specific inhibitor (z-ITED-fmk, ited) all remarkably inhibited XL388-induced MG-63 cell apoptosis (TUNEL assay, Figure 2D).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations